Disproportionate effect on child admissions of the change in Medicines and Healthcare Products Regulatory Agency guidance for management of paracetamol poisoning: an analysis of hospital admissions for paracetamol overdose in England and Scotland - Narayan, Hafid; Thomas, Simon HL; Eddleston, Michael; Dear, James W.; Sandilands, Euan; Nicholas Bateman, D. (British journal of clinical pharmacology, 2015)
Objective The aim of the present study was to assess the effects of the changes in the management of paracetamol overdose recommended by the UK Commission for Human Medicines on rates of hospital admission. Methods An interrupted time series analysis was carried out on data for hospital admissions for paracetamol poisoning for England between January 2010 and June 2014, and for Scotland between January 2010 and Sept. 2014. The main outcome measure was admissions to hospital with paracetamol poisoning (T39.1), as defined by first position coding in children and adults. Results The time series analysis (Jan 2010 to June 2014) showed that admission rates for paracetamol poisoning were steady from 2010 to the date of change (September 2012), with an estimated 269 [95% confidence interval (CI) 252.5, 285.5] child (0–14 years) and 3541 (95% CI 3454, 3628) adult admissions per month. In September 2013, 12 months after the change, there were an estimated additional 116 [37.3% (95% CI 17.2–67.4)] child and 426 [12.5 % (95% CI 4.5–19.6)] adult admissions. Thus, in the year before the change (September 2011 to August 2012) there were 45,181 (3500 child and 41,681 adult) admissions, and in the year after (September 2012 to August 2013) there were 50,198 (4779 child and 45,419 adult) admissions. The overall proportion of child admissions was significantly greater after the change (Chi‐square 32.486, P < 0.001), emphasizing the disproportionate effect in children. Conclusions Changes to the management guidelines for paracetamol poisoning in September 2012 were rapidly implemented but have particularly increased paediatric hospital admissions for paracetamol poisoning. This impact in children, who are at low risk of mortality from paracetamol toxicity, appears excessive.